2021
DOI: 10.1007/s00330-021-07871-4
|View full text |Cite
|
Sign up to set email alerts
|

The splenial angle: a novel radiological index for idiopathic normal pressure hydrocephalus

Abstract: Objectives To evaluate the utility of the splenial angle (SA), an axial angular index of lateral ventriculomegaly measured on diffusion tensor MRI color fractional anisotropy maps, in differentiating NPH from Alzheimer’s disease (AD), Parkinson’s disease (PD), and healthy controls (HC), and post-shunt changes in NPH, compared to Evans’ index and callosal angle. Methods Evans’ index, callosal angle, and SA were measured on brain MRI of 76 subjects comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Measures of WM structural deformation and integrity measured through DTI have also been shown to distinguish between NPH and PD. The SA introduced by Chan et al ( 30 ) was significantly higher in NPH versus PD. Kanno et al ( 65 ) found lower FA and higher MD in the supratentorial WM in NPH when compared to PD.…”
Section: Parkinson’s Diseasementioning
confidence: 88%
See 2 more Smart Citations
“…Measures of WM structural deformation and integrity measured through DTI have also been shown to distinguish between NPH and PD. The SA introduced by Chan et al ( 30 ) was significantly higher in NPH versus PD. Kanno et al ( 65 ) found lower FA and higher MD in the supratentorial WM in NPH when compared to PD.…”
Section: Parkinson’s Diseasementioning
confidence: 88%
“…A novel measure called the Splenial Angle (SA), defined on Diffusion Tensor Imaging (DTI) MRI Fractional Anisotropy maps as the angle subtended by the forceps major of the corpus callosum (CC) on axial slices, to capture the effect of ventricular distention on the CC at the ML in probable NPH was shown to have high sensitivity in distinguishing it from controls ( 30 ). Left ear extinction in NPH possibly associated with the upward elevation and thinning of the CC was found to be alleviated among patients with NPH post shunting, indicating the range of impairments that may be reversed with surgery ( 59 ).…”
Section: Normal Pressure Hydrocephalusmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [11] reported that the combination of the narrowing of the callosal angle (CA), the dilatation of the Sylvian fissure and the narrowing of superior parietal sulci could be useful in the differential diagnosis between iNPH and AD (AUC 0.89). Chan et al [12] reported that the splenial angle presented higher accuracy than EI and CA in differentiating iNPH from AD (AUC 0.98).…”
Section: Discussionmentioning
confidence: 99%
“…Based on CT image features, it included seven items: the EI, Sylvian fissures, tight high convexity, CA, focal sulcal dilatation, temporal horns, and periventricular hyperintensities (PVH) [ 9 ]. However, the accuracy and practicability of traditional structural imaging in the diagnosis and prognosis of iNPH are still debated [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%